PENGARUH PROFITABILITAS, LEVERAGE, UKURAN PERUSAHAAN DAN KUALITAS AUDIT TERHADAP MANAJEMEN LABA DI BURSA EFEK INDONESIA - Feny Mardianto; Agus Defri Yando (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2020)
The purpose of this research is to test whether suspected variables such as profitability, leverage, company size and audit quality have an impact on earning management. secondary data was used in this research, Population in this research was 45 companies from banking company listed on Indonesia Stock Exchange from period 2015 – 2019, data is collected by documentation method, where data is accumulated from financial statements. 28 samples obtained with purposive sampling technique. This research outcome shows that profitability, leverage, and audit quality has significant negative impact on earning management while firm size variable has significant positive impact on earning management and simultaneous profitability, leverage, firm size and audit quality have an impact on earning management